DNA hypermethylation in Drosophila melanogaster causes irregular chromosome condensation and dysregulation of epigenetic histone modifications. - Weissmann, F.; Muyrers-Chen, I.; Musch, T.; Stach, D.; Wiessler, M.; Paro, R.; Lyko, F. (Molecular and Cellular Biology, 2003)
The level of genomic DNA methylation plays an important role in development and disease. In order to establish an experimental system for the functional analysis of genome-wide hypermethylation, we overexpressed the mouse de novo methyltransferase Dnmt3a in Drosophila melanogaster. These flies showed severe developmental defects that could be linked to reduced rates of cell cycle progression and irregular chromosome condensation. In addition, hypermethylated chromosomes revealed elevated rates of histone H3-K9 methylation and a more restricted pattern of H3-S10 phosphorylation. The developmental and chromosomal defects induced by DNA hypermethylation could be rescued by mutant alleles of the histone H3-K9 methyltransferase gene Su(var)3-9. This mutation also resulted in a significantly decreased level of genomic DNA methylation. Our results thus uncover the molecular consequences of genomic hypermethylation and demonstrate a mutual interaction between DNA methylation and histone methylation.